2004
DOI: 10.1051/0004-6361:20035959
|View full text |Cite
|
Sign up to set email alerts
|

The Geneva-Copenhagen survey of the Solar neighbourhood

Abstract: Abstract. We present and discuss new determinations of metallicity, rotation, age, kinematics, and Galactic orbits for a complete, magnitude-limited, and kinematically unbiased sample of 16 682 nearby F and G dwarf stars. Our ∼63 000 new, accurate radial-velocity observations for nearly 13 500 stars allow identification of most of the binary stars in the sample and, together with published uvbyβ photometry, Hipparcos parallaxes, Tycho-2 proper motions, and a few earlier radial velocities, complete the kinemati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

184
2,121
23
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,583 publications
(2,335 citation statements)
references
References 78 publications
184
2,121
23
1
Order By: Relevance
“…From spectral analysis of the SOPHIE data using the method presented in Santos et al (2004), we derived T eff = 5608 ± 20 K, log g = 4.51 ± 0.10, [Fe/H] = −0.02 ± 0.03, and M * = 0.86 ± 0.06 M , which agrees with values from the literature. For the temperature and the mass, the values we adopt in Table 1 are compromise values between ours and those obtained by Nordström et al (2004) (T eff = 5636 K and M * = 0.91 +0.08 −0.04 M ). We derive v sin i = 2.8 ± 1.0 km s −1 from the parameters of the CCF using a calibration similar to those presented by Santos et al (2002), in agreement with the value v sin i = 3 kms −1 from Nordström et al (2004).…”
Section: Stellar Properties Of Hd 16760mentioning
confidence: 98%
See 1 more Smart Citation
“…From spectral analysis of the SOPHIE data using the method presented in Santos et al (2004), we derived T eff = 5608 ± 20 K, log g = 4.51 ± 0.10, [Fe/H] = −0.02 ± 0.03, and M * = 0.86 ± 0.06 M , which agrees with values from the literature. For the temperature and the mass, the values we adopt in Table 1 are compromise values between ours and those obtained by Nordström et al (2004) (T eff = 5636 K and M * = 0.91 +0.08 −0.04 M ). We derive v sin i = 2.8 ± 1.0 km s −1 from the parameters of the CCF using a calibration similar to those presented by Santos et al (2002), in agreement with the value v sin i = 3 kms −1 from Nordström et al (2004).…”
Section: Stellar Properties Of Hd 16760mentioning
confidence: 98%
“…For the temperature and the mass, the values we adopt in Table 1 are compromise values between ours and those obtained by Nordström et al (2004) (T eff = 5636 K and M * = 0.91 +0.08 −0.04 M ). We derive v sin i = 2.8 ± 1.0 km s −1 from the parameters of the CCF using a calibration similar to those presented by Santos et al (2002), in agreement with the value v sin i = 3 kms −1 from Nordström et al (2004). The CCF also allows the value [Fe/H] = 0.06 ± 0.05 to be measured, which agrees with but is less accurate than the metallicity obtained above from spectral analysis.…”
Section: Stellar Properties Of Hd 16760mentioning
confidence: 98%
“…An "n" means that no reliable measurement could be performed for the secondary, either because of a low S/N ratio or due to severe blend between lines of the primary and secondary component. determined by Nordstroem et al (2004) from new accurate radial velocity observations for nearly 13 500 stars. For this purpose the IRAF task fxcor was used.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…The age-metallicity relation (AMR) in the solar neighborhood is still uncertain. Different authors find different relations, ranging from a relatively steep decrease of metallicity with age from Rocha-Pinto et al (2004) to almost no change of mean metallicity with age from Nordström et al (2004). Much of the earlier work indicated that a large scatter in metallicity was seen at all ages, which was part of the motivation to invoke large-scale radial mixing of stars within the disk.…”
mentioning
confidence: 99%